(untitled) - Chang, Sun-Yung Alice (Zurich, 2004)
Non-linear elliptic partial differential equations are an important tool in the study of Riemannian metrics in differential geometry, in particular for problems concerning the conformal change of metrics in Riemannian geometry.
Keywords: Differential equations, Elliptic,Elliptic operators,Phương trình vi phân elip,Toán tử elip